THU0123 Non-Medical Switch from Originator To Biosimilar Infliximab among Patients with Inflammatory Rheumatic Disease – Impact on S-Infliximab and Antidrug-Antibodies. Results from The National Danish Rheumatologic Biobank and The Danbio Registry. (15th July 2016) - Glintborg, B.; Kringelbach, T.; Høgdall, E.; Sørensen, I.J.; Jensen, D.V.; Loft, A.G.; Hendricks, O.; Jensen Hansen, I.M.; Bolstad, N.; Grøn, K.; Eng, G.; Enevold, C.; et al.
Abstract : Background: According to national guidelines issued in 2015, a non-medical switch from originator infliximab (IFX) to biosimilar IFX was conducted in all Danish patients with inflammatory rheumatic diseases treated in routine care. Objectives: To investigate effects of the switch on serum (s) IFX and anti-drug antibodies (ADA) in patients with rheumatoid arthritis (RA), axial spondyloarthrits (SpA) and psoriatic arthritis (PsA). Methods: We included originator infliximab treated patients, who switched to and were treated with biosimiilar infliximab for >2 months with 2 available trough level serum samples (baseline immediately before switching/follow-up 2–4 months after switching time of 2nd–4th infusion). Patients stopping treatment earlier were not included. Trough sIFX <3mg/l was considered low and ≤1mg/l very low. If sIFX <5mg/l, ADA was measured. ADA ≤30AU/l was considered low and ADA >30AU/l median-high. sIFX and ADA were analyzed using automated in-house assays at OUS-Radiumhospitalet. Characteristics and outcomes were registered in the DANBIO registry. Remission was defined by disease activity indices (DAS28 <2.6 (RA, PsA) and ASDAS <1.3 (SpA)). Comparisons were by Mann Whitney U test (unpaired) and Wilcoxon signed rank test (paired). Outcomes are shown as medians (interquartile ranges). Results: 96 pts (192 samples) from 4 departments (49 RA, 27 SpA, 10 PsA, 10 other) were included (age 52 (43–62) years, 47% women). Previous IFX treatment duration was 7.5 (5.1–10.3) years. Follow-up was after 81 (71–90) days. 58 patients (60%) received concomitant methotrexate (15 (10–20) mg/wk). Baseline IFX dose was 3.1 (3.0–4.8) mg/kg every 7 (6–9) weeks. At baseline, 60% of pts had low sIFX and 29% very low and at follow-up it was 57% and 29%, respectively. At baseline, 14 pts (15%) had medium-high ADA, at follow up 16%. Median sIFX was lower at baseline vs. follow-up (1.8 (0.8–5.8) vs 2.4 (0.8–6.2) mg/l, p=0.006) whereas ADA were similar (p=0.7). Six of 58 pts with low baseline sIFX had high sIFX at follow-up, and 3 of 38 pts with high baseline sIFX had low sIFX at follow-up. Similar numbers for low vs. medium–high ADA at baseline and follow-up were 2/81 and 3/15. For the rest, sIFX and ADA remained stable between baseline and follow-up in 87/96 (91%) and 91/96 (95%), respectively (Figure ). MTX use was not associated with sIFX or ADA (both p>0.05). Patients with low sIFX received lower IFX doses than pts with sIFX ≥3mg/l (255 (200–320) mg vs. 300 (250–400) mg, p=0.02) and with longer intervals (8 (6–10) weeks vs. 6 (6–6)weeks, p<0.01). Remission rates at baseline (56%/11%/75%) or follow-up (52%/21%/100%) for RA/SpA/PsA were not associated with sIFX (all p>0.05). Conclusions: In this highly selected group of patients treated with originator infliximab for >5 years, non-medical switch to biosimilar IFX had no negative impact on sIFX or ADA 2–4 months following switch. At baseline, 60% of patients had low sIFX but few patients had ADA, perhaps indicating low immunogenicity in these patients. Disclosure of Interest: None declared